Portfolio optimisation for the Industrial Development Corporation (IDC) - Du Plessis, Charl D. (My University, 2014)
The Industrial Development Corporation (IDC) is South Africa’s largest development financial institution with a stated objective of generating sustainable economic growth across Africa. Additionally, the IDC is also mandated by the South African government to assist in key national development policies. In order to achieve these goals, the IDC seeks to maximise development returns within an acceptable risk portfolio. Using historical data, sector development scorecard analysis and results, and portfolio investment theory, this dissertation examines the investment portfolio weighting to determine if the IDC is positioned to achieve its stated and mandated objectives. The guiding question of this thesis is whether or not the IDC is optimising its capital allocation, and I further seek to identify the sectors in which the IDC should invest in more and the ones the IDC should invest in less in order to achieve maximum development returns. In order to attain an optimal portfolio, the IDC should strive for portfolio selection methodologies as outlined in Markowitz’s Mean-Variance Theory. One of the key benefits of driving this methodology is, depending on the strategic objective, the achievement of an optimised portfolio with predefined constraints. Furthermore the methodology establishes an analytical approach to maximising the strategic objectives.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.